STANDARD-BASED METHOD FOR PROTON-ELECTRON DOUBLE RESONANCE IMAGING OF OXYGEN - Efimova, Olga V. (2011)
Proton-electron double resonance imaging (PEDRI) has been utilized for indirect determination of oxygen concentrations in aqueous samples and living systems. Due to the complexity of the problem, there are seven oxygen related parameters that need to be measured to determine the distribution of oxygen. We present an improved approach in which image intensities from only two PEDRI acquisitions with different EPR irradiation powers are required to determine the distribution of a paramagnetic probe and oxygen in an analyzed sample. This is achieved using three reference samples with known concentrations of a paramagnetic probe and oxygen placed inside the resonator together with the measurement sample. An EPR-off image, which has low signal intensity at low magnetic field (0.02 T) is not required for the calculations, significantly reducing the total time of the experiments and the noise while enhancing the accuracy of these oxygen measurements. The Finland trityl radical was used as the paramagnetic probe and oxygen concentrations could be accurately measured and imaged over the physiological range from 0 to 240 µM.